Kundun e Kumari: A História Encantada do Misterioso Reino de Shangri-La – Contributos para o Estudo da Área Cultural Tibetano-Nepalesa - Fitas, Ana Paula (Trabalhos de Antropologia e Etnologia, 2020)
The main goal of this article is to highlight the similarity of values and practices underlying the social representation of power in culture manifested in the territories that integrate the Nepalese and Tibetan cultural area, with particular emphasis on the construction of traditional social organization processes, the relevance of the child condition and the role of education.